In Vivo Nitroreductase Imaging via Fluorescence and Chemical Shift Dependent 19F NMR. Issue 50 (17th November 2022) - Chen, Shizhen; Xiao, Long; Li, Yu; Qiu, Maosong; Yuan, Yaping; Zhou, Rui; Li, Conggang; Zhang, Lei; Jiang, Zhong‐Xing; Liu, Maili; Zhou, Xin
Abstract: Nitroreductase (NTR) is an important biomarker widely used to evaluate the degree of tumor hypoxia. Although a few optical methods have been reported for detecting nitroreductase at low concentration ranges, an effective strategy for nitroreductase monitoring in vivo without limits to the imaging depth is still lacking. Herein, a novel dual‐mode NIR fluorescence and 19 F MRI agent, FCy7‐NO2, is proposed for imaging tumor hypoxia. We show that FCy7‐NO2 serves as not only a rapid NIR fluorescence enhanced probe for monitoring and bioimaging of nitroreductase in tumors, but also a novel 19 F MR chemical shift‐sensitive contrast agent for selectively detecting nitroreductase catalyzed reduction. Notably, integrating two complementary imaging technologies into FCy7‐NO2 enables sensitive detection of nitroreductase in a broad concentration range without tissue‐depth limit. In general, this agent has a remarkable response to nitroreductase, which provides a promising method for understanding tumor evolution and its physiological role in the hypoxic microenvironment. Abstract : We report a bimodal probe to detect hypoxic tumors by both fluorescence and chemical shift dependent 19 F NMR imaging under the catalysis of nitroreductase. Specifically, the concentration of nitroreductase can be detected in a broad range by fluorescence and 19 F NMR, which is ≤1.5 μg mL −1 and 10–50 μg mL −1, respectively.